Student’s Difficulties in Speaking English: A Qualitative Study at English Course - Fabella Machfira; Nenden Sri Lengkanawati (Lembaga Bale Literasi, 2026)
Speaking is widely regarded as one of the most challenging language skills for English as a Foreign Language (EFL) students, as it requires the students to simultaneously maintain linguistic accuracy, fluency, and social interaction. This study investigates the students’ difficulties when speaking English in an English course, with a particular focus on the interaction between psychological factors and language factors. A qualitative research design was employed in this study. Data were gathered though semi-structured interviews. The findings indicate that students’ speaking difficulties arise from the interaction between psychological and language factors. Psychological factors, including anxiety, fear of making mistake, low self-confidence, and shyness. Meanwhile, on language factors, such as inadequate vocabulary, weak of grammatical competence, and pronunciation difficulties, thereby reducing student’s willingness and ability to communicate. The students had attempted various strategies to overcome their speaking difficulties; however, their efforts had not yet been effective.